OA Repositories @ Special and Academic Libraries in Zagreb - Hebrang Grgić, Ivana (Array, 2009)
The introductory part of the paper deals with the “serial crisis”, the open access movement and the characteristics of the Croatian scientific community. The most important causes of the “serial crisis“ are explained. The open access movement is defined and the most important initiatives, documents and projects are described. Two ways of achieving open access (open access journals and open access repositories) are defined as well. Research on special and academic libraries in Zagreb constitutes the main part of the paper. An electronic online questionnaire has been sent to the libraries of all research institutions in Zagreb that have not yet established their institutional repositories. Librarians were asked whether their institutions should have open access repositories and, if the answer was affirmative, how they think their future repositories should be organized (which software should be used, which formats and types of documents should be deposited, whether they have to be OAI-PMH compliant, how to deal with copyright issues, etc.) The aim of research is to determine how many librarians of special and academic libraries in Zagreb think that institutional repositories are necessary and find out librarians’ opinions on establishing open access repositories. The results show librarians’ awareness of the importance of the open access movement. The results also indicate if there is a need for some national-based plans for action and the funding of institutional open access repositories.